Perkembangan Moral, Fisik, Sosial, dan Intelektual Peserta Didik pada Jenjang SD – SMP – SMA - Hudzaifah Saidi; Mariana Resmisari; Ela Komala (Jurnal Pendidikan Educandum, 2026)
This study aims to analyze strategies for integrating students’ moral development at the elementary (SD), junior high (SMP), and senior high school (SMA) levels with their physical, social, and intellectual development in a comprehensive manner. The research employs a library research method using a descriptive qualitative approach. Data were obtained through a systematic review of relevant national educational literature and academic journals addressing the integration of student development. The findings indicate that the integration of moral development with physical, social, and intellectual aspects can be implemented through value-based learning, the habituation of moral conduct within school culture, reflective-critical approaches in the learning process, and active student participation in religious and social activities. The implementation of these strategies is grounded in the principle of ta’dib, which emphasizes the formation of proper conduct (adab), the internalization of values, and the holistic balance of individual development. This study concludes that integrating moral development with physical, social, and intellectual aspects significantly contributes to character formation, the strengthening of spiritual independence, and the achievement of balanced personality development among students at the primary and secondary education levels.